Factors Associated With Pneumonia Among Overweight and Obese Under-Five Children in an Urban Hospital of a Developing Country. (15th October 2016) - Shahunja, K. M.; Ahmed, Tahmeed; Hossain, Md. Iqbal; Das, Sumon Kumar; Faruque, Abu Syeed Golam; Islam, Md. Munirul; Shahid, Abu Sadat Mohammad Sayeem Bin; Das, Jui; Sarker, Mohammad Habibur Rahman; Chisti, Mohammod Jobayer
To our knowledge, there are no data on the role of overweight and obesity in childhood pneumonia. We sought to determine that impact of overweight and obesity in such children. In this retrospective chart analysis, we enrolled hospitalized children aged 6 to 59 months in the Dhaka Hospital of the icddr, b, Bangladesh (International Centre for Diarrhoeal Disease Research, Bangladesh), from January 2010 to June 2014. Children with pneumonia having overweight and obesity (body mass index Z score [BMIZ] >2.00) constituted cases (n = 25), and those who had pneumonia without overweight and obesity (BMIZ −2.00 to 2.00) constituted controls (n = 75). Controls were 3-fold of the cases and were randomly selected. Demographic, clinical, and laboratory data of the cases and the controls were compared. The cases more often had diarrhea and dehydration (36% vs 12%, P = .013), hypoxemia (SpO2 < 90% in room air; 28% vs 7%, P = .009) on admission, and required to change antibiotics (32% vs 11%, P = .023) during hospitalization compared to the controls. However, in logistic regression analysis the cases were independently associated with diarrhea ( P < .001) and hypoxemia ( P = .024) on admission. Our data suggest that overweight and obesity in children with pneumonia is prone to be associated with hypoxemia on admission, which may guide clinicians in promptly managing pneumonia in order to evade its ramification in such children. However, future research with larger samples is imperative to consolidate or refute our observation.